Universality and Realistic Extensions to the Semi-Analytic Simulation Principle in GNSS Signal Processing - Jakubov, Ondrej; Kacmarik, Petr; Kovar, Pavel; Vejrazka, Frantisek (Společnost pro radioelektronické inženýrství, 2012)
Semi-analytic simulation principle in GNSS signal processing bypasses the bit-true operations at high sampling frequency. Instead, signals at the output branches of the integrate&dump blocks are successfully modeled, thus making extensive Monte Carlo simulations feasible. Methods for simulations of code and carrier tracking loops with BPSK, BOC signals have been introduced in the literature. Matlab toolboxes were designed and published. In this paper, we further extend the applicability of the approach. Firstly, we describe any GNSS signal as a special instance of linear multi-dimensional modulation. Thereby, we state universal framework for classification of differently modulated signals. Using such description, we derive the semi-analytic models generally. Secondly, we extend the model for realistic scenarios including delay in the feed back, slowly fading multipath effects, finite bandwidth, phase noise, and a combination of these. Finally, a discussion on connection of this semi-analytic model and position-velocity-time estimator is delivered, as well as comparison of theoretical and simulated characteristics, produced by a prototype simulator developed at CTU in Prague.
Keywords: AltBOC; BPSK; BOC; GNSS; post-correlation modeling; semi-analytic simulation; tracking loops